Promising new therapies for the treatment of hypercholesterolemia. (3rd May 2016) - Valerio, Marcos G.; Velayati, Arash; Jain, Diwakar; Aronow, Wilbert S.
ABSTRACT: Introduction: Statins are currently the most commonly used agents for treatment of hypercholesterolemia in patients with atherosclerotic cardiovascular disease. However, some patients on statins do not achieve their treatment goals or are intolerant to statins. Therefore, new therapies for treatment of hypercholesterolemia are under investigation. Areas covered: This article reviews the new emerging medications for the treatment of hypercholesterolemia and discusses their efficacy and safety profile based on literature searches that included human studies published on PubMed and reported clinical trials. Expert opinion: Inhibition of the PCSK9 protein by monoclonal antibodies results in a dramatic 40%-60% lowering of serum low-density lipoprotein cholesterol (LDL-C). This is in addition to LDL-C lowering achieved by statins. Multiple clinical studies have demonstrated the high selectivity of these antibodies for the PCSK9 pathway and their long-term safety and efficacy. Alirocumab and evolocumab have been approved by the FDA for the treatment of patients with heterozygous familial hypercholesterolemia and patients with clinical atherosclerotic cardiovascular disease) who do not achieve their LDL-C target on maximal tolerated statin treatment and dietary modification. In addition, evolocumab has been approved by the FDA for homozygous familial hypercholesterolemia. However, the long-term efficacy and safety of PCSK9 inhibitors are unknown.